KARAKTERISASI NANOVESIKEL TRANSFERSOM SEBAGAI PEMBAWA “RUTIN” DALAM PENGEMBANGAN SEDIAAN TRANSDERMAL - Devi Ratnasari; Effionora Anwar (Sekolah Tinggi Teknologi Industri dan Farmasi Bogor, 2016)
Transdermal become the alternative to deliver low solubility compound and low bioavalibility when given orally. Rutin is a flavonoid compound are found in watermelon and citrus. Rutin shows a low absorption when administered orally so the alternative is given in the transdermal route. A variety of approaches taken to increase the penetration of transdermal, one with nanovesikel carrier system. Transfersome is nanovesicle 200-300 nm sized composed of phospholipids, surfactants and water to increase penetration in trasndermal route. This study was to characterization transfersome containing rutin. The result show the size of transfersome < 150 nm, polydispersity index about 0.1 to 0.3, zeta potential less than -30 mV and entrapment efficiency > 80%.